2017
DOI: 10.18632/oncotarget.16831
|View full text |Cite
|
Sign up to set email alerts
|

An injectable nucleus pulposus cell-modified decellularized scaffold: biocompatible material for prevention of disc degeneration

Abstract: We developed a nucleus pulposus cell (NPC)-modulated decellularized small intestinal submucosa (SIS) scaffold, and assessed the ability of this material to prevent Intervertebral disc degeneration (IVD) degeneration. Decellularized porcine SIS was squashed into particles and the biological safety and efficiency of these particles were evaluated. Next, SIS particles were seeded with rabbit NPCs, cultured for two months in vitro, decellularized again and suspended for intervertebral injection. We demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…These constructs have the advantage of maintaining tissue‐specific cell functions and phenotypes to induce host tissue remodelling. Previous studies 23–38 have had success in obtaining aECM scaffolds from virtually all mammalian organs. They preserve the native vasculature for adequate perfusion of constructs able to withstand physiological blood pressures, something that has been a challenge to RM methods relying on progenitor cell embryogenesis 39,40 .…”
Section: State‐of‐the‐art Regenerative Medicine Technologiesmentioning
confidence: 99%
“…These constructs have the advantage of maintaining tissue‐specific cell functions and phenotypes to induce host tissue remodelling. Previous studies 23–38 have had success in obtaining aECM scaffolds from virtually all mammalian organs. They preserve the native vasculature for adequate perfusion of constructs able to withstand physiological blood pressures, something that has been a challenge to RM methods relying on progenitor cell embryogenesis 39,40 .…”
Section: State‐of‐the‐art Regenerative Medicine Technologiesmentioning
confidence: 99%
“…For instance, both the decellularised NP tissue matrix (Fernandez, Marionneaux, Gill, et al, ; Illien‐Junger, Sedaghatpour, Laudier, et al, ) and the NP cell‐derived acellular matrix (Yuan, Yeung, Li, et al, ) were reported to support the viability of endogenous NP cells and the chondrogenesis of exogenous progenitor cells. Porcine small intestine submucosa was found to improve the anabolism of human degenerative disc cells with higher glycosaminoglycan and PGs formation in vitro (Le Visage, Yang, Kadakia, et al, ) and to enhance the hydration and restoration of disc height (DH) in a rabbit model (Shan, Lin, Wang, et al, ).…”
Section: Biomaterial‐based Approach For Ivd Regenerationmentioning
confidence: 99%
“…This review paper summarises the biological approaches to regenerate the degenerated discs either partially or wholly, with cell-laden the viability of endogenous NP cells and the chondrogenesis of exogenous progenitor cells. Porcine small intestine submucosa was found to improve the anabolism of human degenerative disc cells with higher glycosaminoglycan and PGs formation in vitro (Le Visage, Yang, Kadakia, et al, 2006) and to enhance the hydration and restoration of disc height (DH) in a rabbit model (Shan, Lin, Wang, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These suggest that decellularization could produce NP replacement scaffolds with compositions similar to the native ECM, imbuing them with the intrinsic ability to induce NP‐like cell phenotypes while possessing comparable mechanical properties. Decellularized NP therapies have been previously reported, but many are implemented as injectable derivatives of acellular ECM, and have not yet been evaluated for mechanical function postinjection. Decellularization of intact human NP was reported by Huang et al, who demonstrated devitalization of the tissue through the absence of nuclei within lacunae and the preservation of native ECM components .…”
Section: Introductionmentioning
confidence: 99%